2019
DOI: 10.1371/journal.pone.0217697
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory effects on working memory updating development

Abstract: Long-term memory (LTM) associations appear as important to cognition as single memory contents. Previous studies on updating development have focused on cognitive processes and components, whereas our investigation examines how contents, associated with different LTM strength (strong or weak), might be differentially updated at different ages. To this end, we manipulated association strength of information given at encoding, in order to focus on updating pre-existing LTM associations; specifically, association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…In fact, these results suggested that strong associations are dismantled and updated with greater difficulty (i.e., they require longer RTs). A further study (with a developmental sample aged 7–10 years; Artuso and Palladino 2019 ) confirmed adult patterns; indeed, a substantial behavioral cost of dismantling and updating strong associations was shown, regardless of age.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In fact, these results suggested that strong associations are dismantled and updated with greater difficulty (i.e., they require longer RTs). A further study (with a developmental sample aged 7–10 years; Artuso and Palladino 2019 ) confirmed adult patterns; indeed, a substantial behavioral cost of dismantling and updating strong associations was shown, regardless of age.…”
Section: Introductionmentioning
confidence: 55%
“…The relationship between LTM and updating has been investigated rarely, and, to our knowledge, with reference to sub-lexical stimuli only (see Artuso and Palladino 2016 , 2018 , 2019 ). Here, the authors considered literature on the beneficial effects of highly associated LTM information based on lexical and phonological frequencies (see Gathercole et al 1999 ; Hulme et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…previous ndings that highlighted central executive system or EFs as a main component in activation and retrieval of mathematical facts in LTM (46, 69) and that the strength between the EF functions and LTM may be stronger for older children, compared to preschoolers (70).…”
Section: Discussionmentioning
confidence: 92%
“…Although some studies suggest a direct relationship between working memory and long-term memory, 30 , 31 there is a possibility that repeated memorization only triggers the long-term buffer storage capacity (long-term memory) rather than the short-term buffer capacity (working memory). 32 Thirdly, a previous study has shown that working memory capacity may be influenced by the level of an individual's intelligence. 33 Individuals with a high level of intelligence may be able to perform better in the working memory test than those with a standard level of intelligence.…”
Section: Discussionmentioning
confidence: 98%